Comparison of Plankton Abundance, Water Conditions, Performance of Vaname Shrimp (Litopenaeus Vannamei) Growth in Intensive and Extensive Cultivation Systems in Banyuwangi Regency Waters - Ervina Wahyu Setyaningrum; Mega Yuniartik (Journal of Aquaculture Science, 2021)
Vaname is one type of shrimp that is often cultivated in Indonesia. The shrimp farming system model consists of an extensive system (traditional) and an intensive system. This study aims to compare the abundance of plankton, water conditions, growth performance of vannamei shrimp (Litopenaeus vannamei) in intensive and extensive aquaculture systems in the waters of Banyuwangi Regency. Parameters measured include physical and chemical parameters, namely temperature, brightness, pH, dissolved oxygen, salinity, ammonia, and alkalinity, type and abundance of plankton. The research method used is descriptive method. The method of analysis is the abundance of plankton, and analysis of productivity, SR, FCR and growth of vannamei shrimp. The results showed that plankton in intensive pond waters were identified as many as 4 classes, namely phytoplankton class Chlorophyta, Cyanophyta and Chrysophyta, while zooplankton class Protozoa. In traditional ponds, it is not much different, only the Crpytophyta class as an additional identification result. The abundance of plankton in intensive ponds reaches 27,595 individuals per liter, while for extensive ponds the abundance of plankton reaches 37,641 individuals per liter. While the survival rate of shrimp in intensive ponds is around 86%, while in extensive ponds is 67%. The FCR value for extensive ponds is 1.02, while the FCR value for intensive ponds is 1.17. The final average weight of shrimp in intensive ponds was 11.76 g/head and 8.33 g/head in extensive ponds. Keyword : Vaname Shrimp, Intensive Cultivation, Extensive